Congestión vehicular en Medellín: una posible solución desde la Economía (2016)
According to the Economic theory, prices are the most accurate mechanism to solution the traffic congestion problem in urban areas. This article presents a diagnosis on the mobility issue in the city of Medellín (Colombia) and a solution is proposed based on Economic theory. The household expenditures in transportation and the choice between public and private transport were analyzed through the method of elasticity. Evidence has been found proving that the prices mechanism is an efficient mechanism to disincentive the usage of private vehicles, since a rise in the expenditure in transport (due to an hypothetic intra- urban toll) results in a lower probability to use private vehicle and a higher probability to use public transportation.